تأثير العلاج اليدوي مقابل العلاج بالتحفيز الكهربائي في تحسين الألم المزمن الناتج عن الانزلاق الغضروفي العنقي. (Comprehensive Journal of Science, 2025)
The study examined the effectiveness of manual therapy compared with electrical stimulation therapy in reducing chronic pain resulting from cervical disc herniation and improving cervical functional performance. The study relied on a review of previous literature and an analysis of peer-reviewed scientific studies, including clinical trials and systematic reviews published over the past ten years.The results showed that both treatment approaches were capable of reducing pain intensity and improving patients’ psychological status. However, manual therapy demonstrated a relative advantage in terms of faster therapeutic response, improved ability to perform daily activities, and restoration of cervical flexibility and range of motion. In contrast, electrical stimulation therapy contributed more significantly to relieving muscle spasms and improving blood circulation, but it did not achieve full functional recovery to the same extent as manual therapy.The study also indicated that combining manual therapy with electrical stimulation may represent an integrated therapeutic strategy for achieving the best possible outcomes in the management of chronic pain and enhancing patients’ quality of life. Accordingly, the study recommends the use of manual therapy as a primary option for non-surgical treatment, while utilizing electrical stimulation as an adjunct therapy. It further emphasizes the importance of integrating these approaches into routine treatment plans, training physical therapy specialists in their application, and conducting regular patient follow-up to ensure the sustainability of therapeutic benefits. Additionally, the study highlights the need to focus on patients’ psychological health and to develop future hybrid treatment protocols aimed at improving therapeutic outcomes.
Keywords: 1- Manual therapy 2- Electrical stimulation 3- Cervical disc herniation 4- Chronic pain 5- Cervical function